2014
DOI: 10.1016/j.tvjl.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of dorsal hemivertebrae associated with kyphosis by spinal segmental stabilisation, with or without decompression

Abstract: This retrospective case series examined the effectiveness of spinal segmental stabilisation, with or without decompression, in nine dogs with neurological deficits associated with dorsal hemivertebrae. Data on signalment, preoperative neurological status, imaging findings, surgical techniques and outcome were evaluated. All cases occurred in young or adult, small-breed dogs with neurological signs ranging from progressive moderate pelvic limb ataxia to non-ambulatory paraparesis. Six dogs also showed urinary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 23 publications
(52 reference statements)
3
48
1
3
Order By: Relevance
“…Five of the 6 dogs in our case series had concomitant spinal compression of 20%‐50% that was not further addressed. Similarly, Charalambous et al reported 6 dogs with varying degrees of vertebral canal stenosis (27%‐88%) that did not undergo decompressive surgery but underwent only stabilization of the kyphotic segment and reached a satisfactory outcome. Findings of our case series combined with Charalambous and colleagues’ experience could indicate that instability of the kyphotic segment is an important component in the chronic progression of the clinical signs in dogs with thoracic kyphosis and secondary myelopathy.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Five of the 6 dogs in our case series had concomitant spinal compression of 20%‐50% that was not further addressed. Similarly, Charalambous et al reported 6 dogs with varying degrees of vertebral canal stenosis (27%‐88%) that did not undergo decompressive surgery but underwent only stabilization of the kyphotic segment and reached a satisfactory outcome. Findings of our case series combined with Charalambous and colleagues’ experience could indicate that instability of the kyphotic segment is an important component in the chronic progression of the clinical signs in dogs with thoracic kyphosis and secondary myelopathy.…”
Section: Discussionmentioning
confidence: 95%
“…All dogs underwent a full neurological examination at initial presentation and several times postsurgery. A grading scale created by Charalambous et al was applied to assess gait abnormalities and neurological deficits in each dog, allowing comparisons among various consultations (Table ). The same neurologist (RC) assessed the neurological function of each dog from initial presentation to the last follow‐up examination.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations